Politics of Ethno-Nationalism: A Post-Colonial and Post-Socialist Schema - Allahar, Anton L. (Sociologija. Mintis ir veiksmas, 2008)
The present paper aims to propose a schema for analysing the contemporary politics of national and ethnic identity in post-colonial and post-socialist states. To this end it will seek: (a) to provide a comprehensive operational definition of nationalism, (b) to qualify that definition by the addition of the adjective ‘ethnic,’ (c) to assess the extent to which the concept ‘ethnic nationalism’ can help us to understand some of the politics of ethnicity and national identity in a post-independence setting, and (d) to problematize the notion of ‘false consciousness’ in ethno-national political appeals. My argument will be situated within the broad theoretical framework of a non-reductionist, neo-Marxist class analysis, for it is my conviction that ethno-national consciousness and politics are better understood if we are able to trace the concrete class interests and motives of their promoters. In other words, whether as sentiment or as movement, nationalism cannot be divorced from the class interests of its leading promoters. But one must be cautious when absolutizing the class claim, for in the specific case of ethnic nationalism, for example, Robin Williams has noted that “to dismiss ethnicity as false consciousness ignores the clear evidence that ethnies often sacrifice economic interests in favour of symbolic gains” (1994:64-65), and even beyond this, as Ronaldo Munck reminds us, “nationalism matters because people die for it” (1986:2).